“Canción con todos”: América Latina e interculturalidade no livro didático de Espanhol - PNLD/2018 - Adriana Teixeira Pereira (2021)
“I am twenty-five years old of dreams and blood, and of South America”, sang Belchior. But do we Brazilians recognize ourselves as South Americans and/or Latin Americans in fact? How is this identity construction addressed in teaching Spanish, precisely in textbooks? As this is a great provider of information and speeches, it directly affects the student's identity construction, thus needing to present a view of the language plurality and heterogeneity and its manifestations without being linked to stereotypes and prejudices towards different cultures, encouraging dialogue and respect for diversity. Therefore, this study aims to analyze the cultural image of Latin America in the didactic collections approved by the National Textbook Program/2018, from an intercultural perspective, in order to also contribute to the discussion about the idea of belonging to this space. The research is characterized as qualitative, interpretative and documental, since it focuses on a corpus construction formed by Spanish language textbooks, interpreted through content analysis (BARDIN, 2011). The research comprises a corpus of nine volumes from the collections Cercanía joven (COIMBRA; CHAVES, 2016), Confluencia (PINHEIRO-CORREA et al, 2016) and Sentidos en lengua española (FREITAS; COSTA, 2016), addressed from the central foundation’s aspects - Latin America and interculturality. The analysis focused on oral/written texts and their activities, highlighting different aspects of the Latin American identity construction and the guidance of an intercultural perspective of language teaching, being understood as a proposal that provides openness to others, to dialogues and to the cultural, social, ethnic, age and gender diversities of the Latin American peoples. As a theoretical foundation, it is based on Candau’s interculturality studies (2008, 2010), Fleuri’s (2003, 2004, 2012), Mendes’ (2007, 2011, 2012) and Walsh’s (2005; 2009); on Bethel’s Latin American concepts (2009), Bruit’s (2000), Farret’s; Pinto’s (2011), García Canclini’s (2015, 2004), Mignolo’s (2005) and Pizarro’s (2006) and on Barros et al’s Didactic Book (2018) and Daher et al’s studies (2013). From the analysis, a relevant advance was observed in each collection under the two aspects analyzed. As for the presence of LA in the collections, the possibility of dealing with different knowledges that allow students to expand their understanding was noted. Reflecting on the diversity that makes up this space, however, does not correspond to the notion of integration, by failing to relate the contents with the student's reality, derailing the perception of sharing stories, memories, values, experiences and meanings that make them understand themselves as belonging to the same cultural space. Regarding the intercultural perspective, the texts and their activities have displayed great potential for promoting a critical and intercultural attitude of the students. A vast potential for respectful and egalitarian dialogue between cultures was observed, for confronting and facing conflicts of power and for combating stereotypes, prejudices and discrimination. Thus, this research is expected to offer contributions to expand discussions on LA and interculturality within the scope of Spanish language studies in Applied Linguistics, calling for them to be carried out in our teaching practices and socio-cultural relations.